Proteomic and transcriptomic analyses to explain the pleiotropic effects of Ankaferd blood stopper. (26th July 2017) - Simsek, Cem; Selek, Sebnem; Koca, Meltem; Haznedaroglu, Ibrahim Celal
Ankaferd blood stopper is a standardized mixture of the plants Thymus vulgaris, Glycyrrhiza glabra, Vitis vinifera, Alpinia officinarum, and Urtica dioica and has been used as a topical hemostatic agent and with its clinical application established in randomized controlled trials and case reports. Ankaferd has been successfully used in gastrointestinal endobronchial mucosal and cutaneous bleedings and also in abdominal, thoracic, dental and oropharyngeal, and pelvic surgeries. Ankaferd's hemostatic action is thought to form a protein complex with coagulation factors that facilitate adhesion of blood components. Besides its hemostatic action, Ankaferd has demonstrated pleiotropic effects, including anti-neoplastic and anti-microbial activities and tissue-healing properties; the underlying mechanisms for these have not been well studied. Ankaferd's individual components were determined by proteomic and chemical analyses. Ankaferd also augments transcription of some transcription factors which is shown with transcriptomic analysis. The independent effects of these ingredients and augmented transcription factors are not known precisely. Here, we review what is known of Ankaferd blood stopper components from chemical, proteomic, and transcriptomic analyses and propose that individual components can explain some pleiotropic effects of Ankaferd. Certainly more research is needed focusing on individual ingredients of Ankaferd to elucidate their precise and effects.